Kebijakan Kepolisian Resor Tomohon dalam Mencegah Pelanggaran Lalu Lintas dan Angkutan Jalan di Kota Tomohon - Steven Rafvael Christian Simatupang; Jetty E. H. Mokat; Devie S. R. Siwij (Tumoutou Social Science Journal, 2026)
This study aims to analyze the policies of the Tomohon District Police (Polres Tomohon) in preventing traffic and road transport violations in Tomohon City. A qualitative descriptive approach was employed, with data collected through field observation, in-depth interviews, documentation, and literature review.Data were analyzed through successive stages of data reduction, data presentation, and conclusion drawing. The findings reveal that Tomohon Police's policies are implemented through two principal approaches: preventive measures, including roadside vehicle inspections; and repressive measures, encompassing violation enforcement, follow-up investigations, and legal proceedings ranging from traffic citations to court trials. Despite yielding reasonably positive outcomes, policy implementation continues to face notable challenges, including limited personnel, insufficient public legal awareness, and uncooperative behavior from certain violators in the field. This study concludes that policy effectiveness needs to be strengthened through more intensive public outreach programs, continuous improvement of community legal awareness, and the optimization of law enforcement mechanisms in order to achieve orderly, safe, and unimpeded traffic conditions in Tomohon City.